Crowdsourcing Web Model of Product Review and Rating Based on Consumer Behaviour Model Using Mixed Service-Oriented System Design - Yuli Adam Prasetyo (IC-ITECHS, 2014)
The existence of internet drives many consumer behavior changes. Purchase online (e-commerce) is growing rapidly led to the assumption of behavioral changes prior to making a purchase. Consumer behavior models are 5 phases from needs identification, information search, alternative evaluation, purchase decision, and post-behavior. This model is phases of before and after purchase including online purchasing behavior. Product information has spread on the internet in the form of blogs, web commerce, or other. Buyer candidate need a lot of time to search product information from previous users. Therefore, we need web as a bridge that can bring together the information from experienced users and the need of product from buyer candidate. The concept of crowdsourcing is the right solution to be that bridge web.This study aimed to find the crowd sourcing model of product review and rating based on consumer behavior model. Research methods include surveys, interviews and literature studies. Results of the research is a crowd sourcing model of web of product review and rating using the concept of a mixed service oriented system.This concept is a blend of Software-Based Services (SBS) and Human-Provided Services (HPS). The design of this model can be applied in the development of web-based crowdsourcing